Is cabri 3d software effective for teaching geometry materials? A meta-analysis study in Indonesia - Suparman Suparman (Journal of Advanced Sciences and Mathematics Education, 2021)
This study aims to examine the effect of Cabri 3D software in teaching geometry material and explore some potential factors moderating the heterogeneity of students' mathematical academic outcomes. A meta-analysis by selecting the random effect model was employed in this study. The final literature search and selection process determined eight journal articles and six proceeding articles published from 2016 to 2021 and indexed by Scopus and Google Scholar. Numerical and categorical data of every document were extracted to a coding sheet. Data were analyzed by using the Z-test and the Q Cochran test. The tests were assisted by the Comprehensive Meta-Analysis (CMA) software. The result showed that the overall effect size of the Cabri 3D software in teaching geometry materials was g = 0,635. It meant that Cabri 3D software posed a moderately positive effect on students' mathematical learning outcomes in geometry learning. Moreover, Cabri 3D software was significantly effective for teaching geometry material. Some potential factors, such as education level, participant number, and treatment duration, did not moderate the heterogeneity of students' mathematical academic outcomes. This study suggests that mathematics teachers or lecturers utilize Cabri 3D software to teach geometry materials.